معان جديدة عصرية في صرف أموال الزكاة في تفسير المنار - Adnan Mohd. Yusoff; Rabi'atul Adawiyyah Muhammad; Nur Zulaili Muhammad Ghazali; Nur Hasniza Ibrahim; Nurullisza Kasim; Abdoul Karim Toure (Universiti Sains Islam Malaysia, 2024)
The aim of this study is to elucidate the perpetuity and validity of the Holy Qur'an. The Qur'an is the last divine scripture revealed to the whole mankind since one thousand four hundred years ago. Despite its old history, its teachings and wisdoms remain relevant in every aspect of modern life, be it political, social or economic. Having based the study on an inductive method, the researchers elaborated Verse 60 of Surah Al-Taubah, in which, Rasyid Ridha had introduced the new interpretation regarding the Zakat distribution in his Tafsir Al-Manar. The findings from this research are; even though the time has always changed, the Qur'an is not obsolete. Its teachings remain compatible with humans' life from generations to generations. This research also affirms the fact that Islam provides the best remedy and solutions for all dealings in humans' life including for the contemporary issues faced by them.